İlhan Berk'in şiirlerinde anneye dönüş arzusu - Öztürk, Veysel. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
When it IS compared with his contemporaries, ilhan Berk has espoused imprecise style III poetry. This understanding of poetry brings in its train the infiltration of content of the uncounsciousness to the text of poem consistently. Psychoanalytic criticism which aims to analyze unconsciousness of the poet and the text enables re-fictionalization and re-interpretation of the work. In this regard, in order to interpret works of ilhan Berk, it is inevitable to take what opportunity is presented by psychoanalytic criticism that intends to explore uncounscious of the text of poetry. When approaching to ilhan Berk's poetry, one says that the main desire in his works is "desire of the return to the mother." That desire shows itself in two forms as "the return to the womb of mother" and "the return to the early childhood in which child and mother were unified." "Desire of the return to the mother" could be followed by means of four main themes in his poems which are "loneliness" "sexual intercourse", "sea" and "death." Loneliness does not only express an experience which is peculiar to the persona who lost his mother, but also at the same time the loss of a bygone transcendental identity of the mother ad infinitum who has her child snatched to the world of culture. Nonetheless, "sexual intercourse", "return to the sea" and "death" are uncounscious ways that were invented by the persona in order to compensate for his separation from the mother. The aim of this study is to pursue "desire of the return to the mother" by means of psychoanalytic criticism in ilhan Berk's works who is one of the outstanding poets in Turkish literature. Vlll
Keywords: Poets, Turkish -- 20th century.